Meat processing wastewater; the use of Lemna minor L. to convert an environmental burden into a new resource - Sasmaz Kislioglu, Merve; Katsara, Alexandra; Redmond, Cian; Drenckhan, Wiebke; Jansen, Marcel A. K. (Frontiers in Environmental Science, 2025)
The meat processing industry generates a considerable amount of meat processing wastewater (MPW) that is potentially harmful when released in the natural environment. Therefore, current industry practices involve extensive MPW remediation before release of effluent into local waters. Here, it was investigated whether aquatic duckweed (Lemna minor L.) can be used to remediate and retain nitrogen and phosphorus present in MPW that had undergone primary and secondary treatment. Physicochemical analyses, as well as laboratory and glasshouse growth trials, show the suitability of MPW as a growth medium for duckweed. Quantitative analysis revealed that duckweed growth on MPW is associated with rapid removal of nitrogen and phosphorus with calculated uptake rates similar to those reported in the literature. Longer term cultivation on MPW (>6 days) led to increased salinity problems, however, short-term (3 days) remediation of MPW was found to be sufficient to achieve wastewater discharge requirements. Thus, a duckweed-based system can be used to remediate MPW. The suitability of duckweed biomass as a source of protein, bioenergy and/or fertiliser will facilitate retention of plant nutrients within the agri-feed sector in line with the principles of the circular economy and constitute a promising avenue towards more sustainable meat processing. Future work needs to focus on upscaling duckweed remediation under realistic industry conditions, while exploring technical (salinity and seasonality), economic (cost-benefit), social, regulatory and sanitary aspects.